Pengaruh Penggunaan AKM Program Kampus Mengajar Hasil Belajar Literasi Numerasi Siswa SDN Latang - Fahrul Donumo; Sri Hastati; Ince Prabu Setiawan; Erniati Erniati; Erwin Nurdiansyah (DIKDAS MATAPPA: Jurnal Ilmu Pendidikan Dasar, 2022)
The aim of the researcher in this study is to find out whether there is an effect of using the AKM book on the numeracy literacy learning outcomes of SDN Latang students, Alor Regency. This research method uses quantitative methods. This type of research is quasi-experimental research or Quasi-Experimental Design. Quasi-Experimental Design or quasi-experimental, namely research carried out without a comparison class or control class. The results of the study showed that before being given treatment, 14 students were obtained in the sufficient category with a presentation of 46.7%, in the less category there were 7 students with a presentation of 23.33%, and in the very poor category, there were 9 students with a presentation of 30% so as to obtain an average the average value of the pretest is 60.50. After being given treatment, 2 students were in very good category with a presentation of 6.7%, in the good category, 15 students were obtained with a 50% presentation, in the sufficient category, 11 students were obtained with a presentation of 36.7% and in the poor category, there were 2 with a presentation of 6.7 %, thus obtaining the average Posttest score.